COMMUNITY PARTICIPATION IN TOURISM MANAGEMENT OF AYUTTHAYA HISTORICAL PARK - ชื่นบุญ อัชฌา; โสตถิวรรณ์ ธิปัตย์; โลลุวิวัฒน์ รุ่งฤดี; ช่วยพิทักษ์ วริทธ์นันท์ (Sripatum Review of Humanities and Social Sciences, 2018)
The objectives of this research are (1) to study the satisfaction of tourists who came to visit Ayutthaya Historical Park; (2) to study the community participation in tourism management of Ayutthaya Historical Park; and (3) to study the problems of community participation in tourism management of Ayutthaya Historical Park. The researchers employed a questionnaire and interviews to collect research data from the research sample consisting of 145 representatives of state agencies, representatives of sub-district administrative organizations, community leaders, vendors, people and youths in the historical park area, and 400 foreign tourists visiting Ayutthaya Historical Park. Qualitative research data were analyzed with content analysis for description and connection of information; while quantitative research data were statistically analyzed using the frequency, percentage, mean, and standard deviation. The findings were as follows: Findings from analysis of quantitative data: (1) the satisfaction of tourists with visiting Ayutthaya Historical Park was at the moderate level; (2) the overall participation of community in tourism management of Ayutthaya Historical Park was at the low level, as perceived by representatives of state agencies, representatives of sub-district administrative organizations, community leaders, vendors, people, and youths in the historical park area; and (3) the overall problem of community participation in tourism management of Ayutthaya Historical park was at the low level, as perceived by representatives of state agencies, representatives of sub-district administrative organizations, community leaders, vendors, people, and youths in the historical park area. Findings from analysis of qualitative data: the community leaders, representatives from educational institutions, representatives from state agencies, vendors, and people perceived that they lacked participation in tourism management; there was a lack of coordination and cooperation among work agencies; and a lot of problems on tourism management of Ayutthaya Historical Park were not remedied resulting in tourism management of Ayutthaya Historical Park being difficult to manage. The suggested guidelines for tourism management of Ayutthaya Historical park were the following: every sector should participate in bringing the strengths of the Historical part to attract the tourists to visit it on a continuous basis; the state sector should put more efforts in promotion of tourism and remedying the existing weaknesses by allocating more budgets, personnel, and encouraging the people to mutually take care of historical sites to prevent them from deteriorating, and mutually restore historical sites after the occurrence of natural disasters in order to achieve continuous and sustainable development.